2017
DOI: 10.1186/s40317-017-0123-1
|View full text |Cite
|
Sign up to set email alerts
|

Super machine learning: improving accuracy and reducing variance of behaviour classification from accelerometry

Abstract: Background: Semi-automating the analyses of accelerometry data makes it possible to synthesize large data sets. However, when constructing activity budgets from accelerometry data, there are many methods to extract, analyse and report data and results. For instance, machine learning is a robust approach to classifying data. We used a new method, super learning, that combines base learners (different machine learning methods) in an optimal manner to achieve overall improved accuracy. Other facets of super learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 32 publications
2
58
0
Order By: Relevance
“…Our results, with a Resheff et al (2014) reported 84.02% accuracy for six behaviours in griffon vultures, Graf et al (2015) reported 94.99% accuracy for six behaviours in Eurasian beavers, Castor fiber, and Nathan et al (2012) reported 90.88% accuracy for seven behaviours in griffon vultures. As in previous comparative studies (Nathan et al, 2012;Ellis et al, 2014;Resheff et al, 2014;Ladds et al, 2017), the Random Forest algorithm performed better than the CART algorithm, with specific improvement being manifest in the precision and recall indices of the behaviours: here, the global accuracy was 5.66 points higher with the Random Forest algorithm in the hawksbill and green turtle model, and 7.2 points higher in the loggerhead turtle model. In both cases, the behaviours that showed some difficulty in identification by the CART algorithm were associated with a greater increase of one, or both, of the indices in the Random Forest model.…”
Section: Discussionsupporting
confidence: 77%
“…Our results, with a Resheff et al (2014) reported 84.02% accuracy for six behaviours in griffon vultures, Graf et al (2015) reported 94.99% accuracy for six behaviours in Eurasian beavers, Castor fiber, and Nathan et al (2012) reported 90.88% accuracy for seven behaviours in griffon vultures. As in previous comparative studies (Nathan et al, 2012;Ellis et al, 2014;Resheff et al, 2014;Ladds et al, 2017), the Random Forest algorithm performed better than the CART algorithm, with specific improvement being manifest in the precision and recall indices of the behaviours: here, the global accuracy was 5.66 points higher with the Random Forest algorithm in the hawksbill and green turtle model, and 7.2 points higher in the loggerhead turtle model. In both cases, the behaviours that showed some difficulty in identification by the CART algorithm were associated with a greater increase of one, or both, of the indices in the Random Forest model.…”
Section: Discussionsupporting
confidence: 77%
“…For both species, including more than two or three predictor variables gave no significant improvement in classification accuracy. Many other studies, particularly those using machine learning methods, include large numbers of predictor variables (Ladds et al, ; Nathan et al, ). We found that limiting the number of variables greatly reduced analysis time, because files are smaller and models are simpler.…”
Section: Discussionmentioning
confidence: 99%
“…That classification accuracy was consistently high is perhaps not a surprising result. Many studies have found higher accuracy when only a small number of general behaviors is considered (Hammond, Springthorpe, Walsh, & Berg‐Kirkpatrick, ; Ladds et al, ; Shamoun‐Baranes et al, ). Indeed, the behaviors we considered are readily identifiable in an accelerometer trace using the human eye.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations